If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2(x + -1) = 4 + -3(x + -2) Reorder the terms: x + -2(-1 + x) = 4 + -3(x + -2) x + (-1 * -2 + x * -2) = 4 + -3(x + -2) x + (2 + -2x) = 4 + -3(x + -2) Reorder the terms: 2 + x + -2x = 4 + -3(x + -2) Combine like terms: x + -2x = -1x 2 + -1x = 4 + -3(x + -2) Reorder the terms: 2 + -1x = 4 + -3(-2 + x) 2 + -1x = 4 + (-2 * -3 + x * -3) 2 + -1x = 4 + (6 + -3x) Combine like terms: 4 + 6 = 10 2 + -1x = 10 + -3x Solving 2 + -1x = 10 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + -1x + 3x = 10 + -3x + 3x Combine like terms: -1x + 3x = 2x 2 + 2x = 10 + -3x + 3x Combine like terms: -3x + 3x = 0 2 + 2x = 10 + 0 2 + 2x = 10 Add '-2' to each side of the equation. 2 + -2 + 2x = 10 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 10 + -2 2x = 10 + -2 Combine like terms: 10 + -2 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 | | 5m=10-5m | | 3(x+15)+4(9-x)=0 | | 8r=-4r-12 | | x^2-6=55 | | 0.2x+9=8(0.4x-1) | | -2=3n+6-5n | | 244.92=2r*3.14 | | -3+2x=3x-4 | | 9(3x-1)-5=6x | | 8x-5=-2x+1 | | 2+3x=6+4x |